THE DETERMINANTS OF CUSTOMER LOYALTY IN RETAIL INDUSTRY - Fitrianingrum, Agustina (Program Sarjana Manajemen Universitas Internasional Batam, 2020)
Customer loyalty is the core of business sustainability. In the disruptive era of digital business, it is important for the conventional retail business industry to focus on some determining factors that influence customer loyalty. This study finds that physical aspects and problem-solving are considered giving a significant contribution to building customer loyalty in the Retail Industry in Indonesia. The physical aspect that creates positive moods and security is expected by every potential customer especially in conventional business retail. The ability to solve the problem of the customers is building a positive relationship with the customers and could be the driver of positive mood and it strengthens future customer loyalty.